Levels of PAHs in the Waters, Sediments, and Shrimps of Estero de Urias, an Estuary in Mexico, and Their Toxicological Effects - Foday M. Jaward; Henry A. Alegria; Jose G. Galindo Reyes; Armando Hoare (The Scientific World Journal)
PAHs were measured in water, sediment, and shrimps of Estero de Urias, an estuary in Sinaloa, Mexico, during the rainy and dry seasons, and analyzed for eleven PAHs routinely detected in samples. Phenanthrene was the most dominant congener in the water, sediment, and shrimp samples comprising about 38, 24, and 25%, respectively, of the eleven PAHs detected, followed by pyrene and naphthalene in water and sediment samples, and pyrene and fluorine in the shrimp samples. Total PAH concentrations ranged from 9 to 347 ng/L in water, 27 to 418 ng/g in sediments, and 36 to 498 ng/g in shrimps. The sources of contamination are closely related to human activities such as domestic and industrial discharge, automobile exhausts, and street runoff. High concentrations were also measured during the rainy season and during the first quarter of the year. Toxicity tests were also carried out, exposing fish embryos and juvenile shrimps to some of these PAHs. Fish embryos exposed to PAHs showed exogastrulation, while juvenile shrimps showed significantly lower growth rates than controls. DNA and protein alterations were also observed. These toxicity tests indicate that PAH concentrations measured could be dangerous to some aquatic organisms, particularly during early stages of development.